Why internet service provider and content provider do not collaborate via monitoring of digital piracy. (December 2017) - Mo, Jeonghoon; Park, Jungju; Im, Nari; Park, Jiwon; Kim, Hansol
Abstract: Internet service providers (ISPs) and content providers (CPs) have a symbiosis relationship in the Internet business ecosystem. In this paper, we investigate the possibility of and the conditions for their revenue sharing by means of on-line content piracy monitoring. CPs can benefit from the efforts of ISPs to monitor illegal content consumers, and can have the incentives to collaborate with ISPs. We suggest that if the quality degradation of a pirated content is low as in real world, there may not be a successful collaboration because CPs have little incentives to share their revenues with ISPs. We also investigated the impacts of ISP's piracy monitoring cost level, the value of contents, and CP's access fee per traffic on the possibility of their collaboration. Highlights: When the content quality degradation rate is low, as in the real world, there may not be successful collaboration between ISPs and CPs. When the content quality degradation is low, CPs can benefit from increasing their access fees per unit traffic. CPs can share their revenue with ISPs when the CPs' access fees per unit traffic are low. Finally, there can be a successful collaboration when consumers' maximum willingness to pay is at a moderate level. ISPs and CPs can collaborate when the piracy monitoring costs of ISPs is at a moderate level.